Classification Of Mediators In The Practice Of Penal Mediation With A Restorative Justice Approach After A Traffic Accident - Arifin, Zainal; Fimaulidina, Noor Rizqiya (Universitas Widya Gama Malang, 2024)
Traffic accidents are a disturbing problem for road users, can cause material and immaterial losses, and are one of the criminal cases that can be resolved through mediation. Penal mediation is a way of handling criminal case disputes involving victims and perpetrators, as well as third parties, namely mediators, without eliminating the principles of restorative justice. The research objective in this article is to examine how mediators are classified based on their role in post-accident criminal mediation mechanisms and examine the juridical basis for implementing criminal mediation in handling traffic disputes. This article uses a juridical-normative research method with a statutory and conceptual approach. The results of this study are, first, that the principle of restorative justice contained in penal mediation has been carried out by the police using the right of discretion contained in the Letter of the Chief of Police Number Pol: B/3022/XII/2009/SDEOPS dated 12/14/2009 concerning handling cases through alternative dispute resolution (ADR). Second, there is no explicit regulation governing penal mediation, but implicitly it has been regulated in Article 1, Number 7, of Law No. 11 of 2012 concerning Juvenile Justice, which is better known as diversion.